Hadis dalam Perspektif Hizbut Tahrir Indonesia (HTI) - Fahrudin (Jalsah : The Journal of Al-quran and As-sunnah Studies, 2021)
This article discusses the thoughts of Hizb ut -Tahrir (HT) on the hadith of the Prophet, especially in relation to the Khilafah. In HT's belief that the hadith of the Prophet related to the baiat and the caliphate is an Islamic teaching that must be fought for, because the Islamic caliphate system has been applied by the Prophet and the khulafaurasyidin and is a concrete proof of the welfare of human life and harmony experienced by society in his time because of upholding Islamic law in kaffah. To be able to describe how HT's view of the hadith, the author collected good literary data from the writings of Taqiyudin al Nabhani himself who was a central figure in the HT group and did not miss the thoughts of his followers or those who opposed HT's own thoughts. . After the author collected some of the necessary data, the author then read and analyzed the thought flow of Hizb ut -Tahrir. By using descriptive analytical methods that eventually produce conclusions based on the results of studies on existing data